A escolarização da literatura para criança e a experiência estética - Trindade, Kethullin Rezende (2017)
This is a study about the viability of children's literature as one of the elements for the event of aesthetic experience in the schooling process. The research was carried out using the exploratory method and the theoretical-bibliographic study in the cultural historical perspective. The interviews were used as instruments of data collection, a questionnaire and observations of the classes in which the object of study was worked. The study sought to analyze and understand if from the practices of Pedagogues of a private school in Goiânia - Goiás with literature for children it would be possible to create aesthetic experiences for infants. Based on the data analyzed, it is possible that the obstacles in relation to the work with the literature for children come from different aspects: teacher training, constitution as a literary reader, reader's conception and working conditions. Through this brief study one can understand that the situation of children's literature in school today remains the same from the studies of decades ago. In view of this observation, it is important to consider that the study of the possibilities of aesthetic experiences with the literary text for children in the schooling process, in pedagogical practice, is substantial for a literary schooling in an adequate way, and mainly contributes to the process Teaching and reading encouragement that is profitable and perennial.